2020
DOI: 10.3390/foods9081044
|View full text |Cite
|
Sign up to set email alerts
|

Towards More Sustainable Meat Products: Extenders as a Way of Reducing Meat Content

Abstract: The low efficiency of animal protein (meat products) production is one of the main concerns for sustainable food production. However, meat provides high-quality protein among other compounds such as minerals or vitamins. The use of meat extenders, non-meat substances with high protein content, to partially replace meat, offers interesting opportunities towards the reformulation of healthier and more sustainable meat products. The objective of this review is to give a general point of view on what type of compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 104 publications
(154 reference statements)
0
29
0
2
Order By: Relevance
“…In the present study, the breast muscle of Cherry Valley broiler ducks at 38 days of age achieved the highest protein content and the relatively lower IMF. The total protein content is an important indicator for meat quality ( Pintado and Delgado Pando, 2020 ), meaning that the meat at 38 d was superior in duck. Also, we observed that total protein content gradually decreased above 38 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the breast muscle of Cherry Valley broiler ducks at 38 days of age achieved the highest protein content and the relatively lower IMF. The total protein content is an important indicator for meat quality ( Pintado and Delgado Pando, 2020 ), meaning that the meat at 38 d was superior in duck. Also, we observed that total protein content gradually decreased above 38 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…The umami flavor of mushrooms offers a dual opportunity to improve the nutritional profile of foods by adding dietary fiber, protein, minerals, and bioactive compounds to foods but also imparting flavors that can complement and enhance the saltiness perception [86]. Reducing salt application in culinary preparations of meat by using the umami properties of Agaricus bisporus without compromising the flavor profile or consumer acceptance was initially investigated by Guinard et al [26] and Myrdal-Miller et al [25].…”
Section: Salt Replacermentioning
confidence: 99%
“…Os produtos cárneos são inerentes à cultura alimentar e são amplamente consumidos em todo o mundo (PINTADO; DELGADO-PANDO, 2020). Versatilidade, produtos mais atraentes, oportunidades de redução de desperdício e vidas úteis mais altas, são algumas das principais características que diferenciam os produtos cárneos (PINTADO; DELGADO- PANDO, 2020). Especiarias, aditivos, agentes aromatizantes, enzimas, açúcares, carboidratos, fibras e produtos proteicos são comumente usados na fabricação desses alimentos (VELEMIR et al, 2020).…”
Section: Produtos Cárneosunclassified